Advances in Head‐Mounted Light‐Field Displays for Virtual and Augmented Reality. Issue 4 (1st July 2016) - Hua, Hong
Abstract : Head‐mounted light‐field displays render a true 3D scene by sampling either the projections of the 3D scene at different depths or the directions of the light rays apparently emitted by the 3D scene and viewed from different eye positions. Head‐mounted light‐field displays are capable of rendering correct or nearly correct focus cues and addressing the well‐known vergence–accommodation mismatch problems of conventional virtual‐ and augmented‐reality displays.